(untitled) (International journal of artificial intelligence, 2024)
This paper explores the various types of corpora and their potential benefits for Uzbek learners of English through the lens of corpus linguistics. It discusses the significance of both written and spoken corpora, as well as specialized corpora tailored to specific fields. The study emphasizes how authentic language data can enhance vocabulary acquisition, grammatical accuracy, and reading comprehension. Additionally, it highlights the role of corpus analysis in fostering self-directed learning and increasing awareness of language variation in different contexts. The aim is to empower Uzbek learners to improve their English proficiency and communication skills in diverse settings.